KONTRIBUSI PROFESI ORANG TUA TERHADAP PEMBENTUKAN KARAKTER RELIGIUS SISWA DI MADRASAH IBTIDAIYAH NIZAMUL ISLAM PROBOLINGGO - Irhamatul Milla; Jadid Khadavi, M.; Khosiah, Nur (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to see the extent of the contribution of parents' professions to the formation of students' religious character at Madrasah Ibtidaiyah Nizamul Islam Probolinggo. Because currently there are more and more phenomena showing that parents have various professions but often forget about the educational process which has implications for the formation of religious character. A qualitative approach is used by researchers because it explores information naturally from phenomena that occur in the field. Data collection was obtained through interviews with informants and Miles & Huberman data analysis was carried out which included three activity streams, namely data reduction, data presentation and drawing conclusions. The conclusions from this research show that parents' professions have a huge impact on the formation of students' religious character. The religious character possessed by students is formed from the example of parents in carrying out daily Islamic teachings, familiarizing themselves with morals, and providing educational rewards for children, thereby creating motivation to always do good.